Talking Toddler: The Psycholinguistic Dynamic of Early Language Acquisition - Setyawan, Wawan; Karyoto (JOSAR (Journal of Students Academic Research), 2024)
An interdisciplinary field called psycholinguistics studies how children speak about what they learn in communication and how their language skills grow as they interact with those around them, revealing psychological processes at work. The psycholinguistic perspective on children's initial language acquisition is the background of this study. The language acquisition process is lengthy and intricate, beginning when a child is non-fluent and continuing until they achieve fluency. This study aims to pinpoint the psycholinguistic processes that underlie young children's language development and how social interactions impact language learning. The study used a qualitative descriptive methodology, utilizing direct observation and parent and child caregiver interviews to gather data. The study's findings indicate that social interaction and the surrounding environment are significant in quickening language learning